2020
DOI: 10.14715/cmb/2020.66.6.22
|View full text |Cite
|
Sign up to set email alerts
|

Urtica dioica agglutinin (a plant lectin) has a caspase-dependent apoptosis induction effect on the acute lymphoblastic leukemia cell line

Abstract: Urtica dioica agglutinin (UDA) is a very small plant lectin with anti-prostatic activity. In this study, we investigated the effect of UDA on proliferation and apoptosis induction in human acute lymphoid leukemia (ALL) cell lines. The effect of UDA on Jurkat and Raji cell proliferation was examined by MTS assay. Distribution of cell cycle phases was determined by PI staining and apoptosis was examined with annexin V/PI and western blot. Results showed UDA treatment reduced cell proliferation in cells by induci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Prior studies have demonstrated that this lectin interferes with the proliferation of various cancer cell lines, including AGS human gastric cancer cells [23], HeLa cervical cancer cells [24], A431 cancer cells [25], and HL-60 cells [25]. Rashidbaghan et al [25] reported an IC 50 value of 400 for UDA against HL-60 cells over 72 h. This difference in cellular response might be due to varia-▶ Fig.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Prior studies have demonstrated that this lectin interferes with the proliferation of various cancer cell lines, including AGS human gastric cancer cells [23], HeLa cervical cancer cells [24], A431 cancer cells [25], and HL-60 cells [25]. Rashidbaghan et al [25] reported an IC 50 value of 400 for UDA against HL-60 cells over 72 h. This difference in cellular response might be due to varia-▶ Fig.…”
Section: Resultsmentioning
confidence: 96%
“…Prior studies have demonstrated that this lectin interferes with the proliferation of various cancer cell lines, including AGS human gastric cancer cells [23], HeLa cervical cancer cells [24], A431 cancer cells [25], and HL-60 cells [25]. Rashidbaghan et al [25] reported an IC 50 value of 400 for UDA against HL-60 cells over 72 h. This difference in cellular response might be due to varia- tions in their gene expression profiles. Notably, PC3 cells exhibit considerably higher expression of HAS2 and HAS3 genes, which influence the synthesis and composition of HA in the extracellular matrix (▶ Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Initially recognized as potent mitogenic proteins [131][132][133], plant lectins have been known for a long time as non-specific immune-modulatory proteins that are susceptible to interaction with various cell surface glycoproteins/glycolipids and for interfering with various signaling pathways triggering cytotopathologic effects on the targeted cells. Although most plant lectins with antiviral activity activate different sets of T lymphocytes and, more scarcely, B lymphocytes, they also activate both the apoptotic and necrotic pathways in many other types of healthy and cancer cells [134][135][136][137][138][139][140][141][142][143]. The cellular activation mediated by plant lectins on healthy and transformed cells elicits the release of various chemokines and/or cytokines that are, in turn, susceptible to interfere with the cytokine stimulation associated with the viral infection, e.g., HIV infection [59].…”
Section: Biomedical Perspectives For Antiviral Lectinsmentioning
confidence: 99%
“…Additionally, Rashidbaghan et al reported that U. dioica extract could inhibit cancer cell migration by regulating certain genes and proteins involved in cell migration and metastasis, such as miR-21, MMP1, MMP9, MMP13, vimentin, CXCR4, and E1. U. dioica root extracts have also been evaluated for their anticancer effects, particularly in human prostate cancer [17]. In another study, U. dioica extract inhibited cell proliferation in NSCLC cell models with low sensitivity to cisplatin, a cytotoxic agent largely employed to cure NSCLCs [18].…”
Section: Introductionmentioning
confidence: 99%